2019
DOI: 10.1016/j.cgh.2018.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Provider Practice Patterns and Barriers to Hepatocellular Carcinoma Surveillance

Abstract: In a web-based survey, PCPs reported misconceptions and barriers to HCC surveillance. This indicates the need for interventions, including provider education, to improve HCC surveillance effectiveness in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 35 publications
3
68
0
Order By: Relevance
“…24,26,27 Provider-level factors such as poor physician-patient communication and inherent provider biases, in addition to system-level factors such as care coordination, available technology, and treatment delays also may play a role. 28,29 Although a prior Veterans Affairs study found that race/ethnicity was not associated with all-cause mortality in HCC, this may be attributable to system-level differences between the Veterans Affairs and the health systems evaluated in our study. 20 In our study, we found that differences in survival were mitigated after adjusting for BCLC tumor stage and receipt of HCC treatment, suggesting that these factors may explain differences in prognosis and be appropriate intervention targets for studies to reduce racial disparities in HCC prognosis.…”
Section: Discussionmentioning
confidence: 56%
“…24,26,27 Provider-level factors such as poor physician-patient communication and inherent provider biases, in addition to system-level factors such as care coordination, available technology, and treatment delays also may play a role. 28,29 Although a prior Veterans Affairs study found that race/ethnicity was not associated with all-cause mortality in HCC, this may be attributable to system-level differences between the Veterans Affairs and the health systems evaluated in our study. 20 In our study, we found that differences in survival were mitigated after adjusting for BCLC tumor stage and receipt of HCC treatment, suggesting that these factors may explain differences in prognosis and be appropriate intervention targets for studies to reduce racial disparities in HCC prognosis.…”
Section: Discussionmentioning
confidence: 56%
“…In clinical practice, primary care providers are often responsible for liver‐related care of cirrhosis patients, particularly in rural areas where access to subspecialty care is limited . Primary care providers report several barriers to HCC surveillance, including inadequate knowledge and clinic time constraints, so it is unclear whether these interventions would be equally effective among these patients . Another study suggested that EMR clinical reminders may increase HCC surveillance among cirrhosis patients followed by primary care providers, but this study relied on visit‐based care and only included patients with documented cirrhosis .…”
Section: Discussionmentioning
confidence: 99%
“…(23) Primary care providers report several barriers to HCC surveillance, including inadequate knowledge and clinic time constraints, so it is unclear whether these interventions would be equally effective among these patients. (24,25) Another study suggested that EMR clinical reminders may increase HCC surveillance among cirrhosis patients followed by primary care providers, but this study relied on visit-based care and only included patients with documented cirrhosis. (26) Our study suggests that mailed outreach invitations can be an effective population health strategy to increase HCC surveillance among at-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we were surprised to observe lower uptake of HCV screening in high‐volume providers with the large baby boomer panels. We initially hypothesized that these providers would be most attuned to the USPSTF recommendations and order HCV screening routinely; however, competing clinical concerns and limited time for preventive care during each visit may have led to low screening uptake . Our intervention was particularly effective among these providers, with significant increases observed in both the postintervention and overlap cohorts, suggesting that this effect occurred across new as well as established patients.…”
Section: Discussionmentioning
confidence: 99%